Heritage, museology and participation: participatory museological strategies in the municipality of Peniche (Cadernos de Sociomuseologia, 2015)
This dissertation is focused on a fieldwork carried out in a parish of Peniche, Portugal, based on a project designated 'Participatory Inventory of Cultural Heritage of Atouguia da Baleia’, associated with the implementation of a museum – the Interpretive Centre of Atouguia da Baleia. It has as objective the inventory of cultural heritage in the different localities of this region, the strengthening of the relation museum-population and the recognition by the community of their assets, concerning the relationship between heritage and development. Developing an action research project, it was implemented a set of participatory museological strategies, in an interdisciplinary perspective, such as tertulias, participatory mapping, transect walks and ethnographic interviews. This project confirmed to be possible, applying the principles of Sociomuseology, the survey, identification and dissemination, as well as recognition and appreciation by the community of its heritage, tangible and intangible. Participation is central in the project. The museum is acknowledged as serving the community and its development, contributing to a better management of local heritage.Keywords: Participatory inventory, Sociomuseology, Cultural heritage, Collective memory, Community development and participation